Safety of dispensing prescribed iron formulation in childresistant containers among pharmacies in Saudi Arabia: a cross-sectional survey - Nahar Alruwaili; Mohammed Alomar; Ismaeel Sabei; Abdelmoneim Eldali (PAGEPress Publications, 2013)
Iron overdose remains a significant public health threat to young children. Unit dose packaging of potent iron supplements is expected to reduce the frequency of severe pediatric iron overdose incidents. Interna - tional regulations require child-resistant iron packages. We aim to know if iron is dispensed in child-resistant containers (CRCs) and to emphasize the importance of using them. A prospective cross-sectional observational study assessing the proper dispensing of ferrous sulfate tablets in CRCs from major city pharmacies. Forty government and private pharmacies were visited. Ferrous sulfates with a total of 600 to 6500 mg elemental iron per package were found. The package of 6000 mg was the most commonly found. Most of the packages with high concentrations are dispensed from the government hospitals and primary healthcare centers pharmacies. None of the pharmacies dispensed iron in CRCs. To conclude, pharmacies dispensed iron in non-CRCs. Public health efforts on increasing awareness and improving packaging are highly needed. Authority regulations to use child-resistant iron packaging are required.